The Political Economy of the GMS Development Between China and Southeast Asian Countries: Geo-Economy and Strategy Nexus. Issue 6 (1st November 2016) - Soong, Jenn-Jaw
Abstract : Following the rise of China, the importance of Greater Mekong Subregion (GMS) has been paid much attention by great powers in East Asia. Since 1992, the Asian Development Bank (ADB) has succeeded in engaging GMS economic cooperation by Japan's dominance. As China emerged and rose in the new century, the GMS spatial development became China's priority for economic extension by way of the "One Belt and One Road" (OBOD) policy and the settlement of the Asian Infrastructure Investment Bank (AIIB). Also, taking the GMS economic corridor as a stepping stone, China will easily be able to connect and integrate the Southeast Asian economy, which is full of political and economic implications. Moreover, it will examine the trade and economic cooperation between China and GMS five countries and their development opportunities. Lastly, through GMS cooperation mechanism and operation, some economic cooperation mechanisms and development strategic logics will be generally concluded.